Immunoadsorption or plasma exchange in steroid‐refractory multiple sclerosis and neuromyelitis optica. Issue 4 (30th January 2019) - Lipphardt, Mark; Mühlhausen, Johannes; Kitze, Bernd; Heigl, Franz; Mauch, Erich; Helms, Hans‐Joachim; Müller, Gerhard A.; Koziolek, Michael J.
Abstract: Background: Plasma exchange (PE) and immunoadsorption (IA) are alternative treatments of steroid‐refractory relapses of multiple sclerosis (MS) or neuromyelitis optica (NMO). Methods: Adverse events and neurological follow‐ups in 127 MS‐ (62 PE, 65 IA) and 13 NMO‐ (11 PE, 2 IA) patients were retrospectively analyzed. Response was defined by improvements in either expanded disability status scale (EDSS) by at least 1.0 or visual acuity (VA) to 0.5, confirmed after 3 and/or 6 months. Results: Hundred and forty patients were included in safety analysis, 102 patients provided sufficient neurological follow‐up‐data. There were no significant differences between IA and PE in side effects (3.9% vs 3.6%, P  = .96) or response‐rate ( P  = .65). Responders showed significant lower age ( P  = .02) and earlier apheresis‐initiation ( P  = .01). Subgroup‐analysis confirmed significant lower age in patients with relapsing‐remitting MS (RRMS) /clinical isolated syndrome (CIS). Conclusion: IA and PE seem equally safe and effective in steroid‐resistant MS‐ or NMO‐relapses. Early apheresis and low patient age are additional prognostic factors.